The allocation of resources from the financial perspective for the agricultural sector in countries of Central and Eastern Europe in 2007-2013 - Fabisiak, Anna; Poczta, Walenty (Rozdysponowanie środków z perspektywy finansowej, przeznaczonych dla sektora rolnego w krajach Europy Środkowej i Wschodniej na lata 2007-2013, 2011)
The membership in the EU offers possibilities of financial support for agriculture and an accelerated economic development of rural areas. This process will continue to be supported from EU funds within the framework of the financial perspective for 2007-2013. It is a chance for further development of agriculture and rural areas in CEEC. It needs to be remembered that a considerable role in the development of the agricultural sector and rural areas is played by the adopted policy concerning them. In the paper, we present the allocation, level, and structure of the financial perspective funds for the agricultural sector in CEEC. What is also compared is the volume of funds in relation to farm, 1 hectare of agricultural area, and 1 person employed in the analyzed sector and their share in GVA. Furthermore, the Ward analysis is conducted
Ekonomia = Economics, 2011, Nr 2 (14), s. 132-140
Keywords: the financial perspective for 2007-2013; agricultural sector; CEEC; EU-25